Heparanase and hepatocellular carcinoma: Promoter or inhibitor? - Dong, Shuo (The WJG Press and Baishideng, 2010)
Heparan sulphate proteoglycans (HSPGs) consist of a core protein and several heparan sulphate (HS) side chains covalently linked. HS also binds a great deal of growth factors, chemokines, cytokines and enzymes to the extracellular matrix and cell surface. Heparanase can specially cleave HS side chains from HSPGs. There are a lot of conflicting reports about the role of heparanase in hepatocellular carcinoma (HCC). Heparanase is involved in hepatitis B virus infection and hepatitis C virus infection, the activation of signal pathways, metastasis and apoptosis of HCC. Heparanase is synthesized as an inactive precursor within late endosomes and lysosomes. Then heparanase undergoes proteolytic cleavage to form an active enzyme in lysosomes. Active heparanase translocates to the nucleus, cell surface or extracellular matrix. Different locations of heparanase may exert different activities on tumor progression. Furthermore, enzymatic activities and non-enzymatic activities of heparanase may play different roles during HCC development. The expression level of heparanase may also contribute to the discrepant effects of heparanase. Growth promoting as well as growth inhibiting sequences are contained within the tumor cell surface heparan sulfate. Degrading different HSPGs by heparanase may play different roles in HCC. Systemic studies examining the processing, expression, localization and function of heparanase should shed a light on the role of heparanase in HCC.